Capital Adequacy Ratio and Profitability: A Case Study of Indian Banks (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This study aims to examine the relationship between capital adequacy ratio (CAR) and profitability of Indian banks. The study analyzes a sample of 15 major Indian commercial banks over a period of 5 years from 2016-2020. Using correlation and regression analysis, the findings indicate a significant positive relationship between CAR and return on assets (ROA) for the overall banking sector. Private sector banks demonstrate a higher correlation between CAR and profitability measures such as ROA and return on equity (ROE) compared to public sector banks. The results highlight the importance of maintaining adequate capital levels for ensuring profitability and financial stability of commercial banks in India. Banks need to focus on improving capital adequacy to support business growth and deliver robust returns to shareholders.